Pesan Kepedulian Video Klip Mantrakama “Cerita Masa Lalu” Terhadap Lingkungan - Fajar Septyano; Suprihatin Suprihatin (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Video clip "The Story of the Past" It is the goal of the band Mantrakama to convey a message about caring for the environment to the public. The reason for researching this video clip is because in the video clip there are several unique features that are displayed and the researcher wants to describe the meaning of the message contained in it. Data was collected using the observation method by watching and documenting in the form of screenshots which the researchers analyzed using qualitative methods with Charles Sanders Peirce's semiotic approach which contains the triangle of meaning, namely Representament, Interpretation, Object. The conclusion of this study is that there are messages related to caring for the environment such as the importance of caring for plants, not littering, reducing air pollution, and caring for fellow humans and the environment.